Biotechnology knowledge and perceptions issues among students in the faculty of agriculture and forestry, University of Ibadan (2013)
This study investigated agricultural students' knowledge and perception of biotechnology issues. The study was carried out at the Faculty of Agriculture and Forestry of the University of Ibadan. Proportionate sampling method was used to select a sample size of two hundred and sixty four (264) respondents. Variables measured included respondents' demographics, biotechnology information sources, knowledge and perception. The data were analyzed using frequencies, percentages and mean for descriptive analysis while Chi-square analysis, Pearson Product Moment correlation and analysis of variance were used for inferential analysis. Findings reveal that 54.5% of the respondents were female, 56.1% of the respondents had negative perceptions towards biotechnology issues while 82.2% of the respondents had average knowledge level on biotechnology issue. A significant relationship exists between each of respondents, years of formal education, (r = 0.122, P = 0.047), religion, x2= 8.015, p = 0.018) department (x2= 23.498, p = 0.024) and their knowledge of biotechnology. Significant difference exists between the knowledge level of the respondents across the sampled departments (F= 3.446, p=0.003). It was concluded that most of the respondents had unfavorable perception and an average knowledge level on biotechnology issues. The study recommends that learning should not be limited to classroom setting alone. Visits to research institute or private firms who are into research on biotechnology should be arranged for students of faculty of agriculture.